2015
DOI: 10.1039/c5ta05995j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyrolysis pressure on activity of Fe–N–C catalysts for oxygen reduction

Abstract: Iron and nitrogen doped carbon, Fe-N-C, catalysts are synthesized by high pressure pyrolysis of Ketjenblack carbon, melamine and iron acetate precursor mixture in a closed, reusable scale-up stainless steel reactor. The effects of precursor loading with constant precursor ratios on obtained pressure, nitrogen retention and oxygen reduction reaction (ORR) activities are studied. The results indicate that higher precursor loading increases the gas phase pressure and improves nitrogen retention and ORR activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
(123 reference statements)
1
21
0
Order By: Relevance
“…Notably, the pyridinic and graphitic nitrogen, considered to be the most efficient active sites of all the nitrogen species in CoO/NC are able to not only enhance the initial chemical adsorption of oxygen on the catalyst surface but increase the number of catalytically active sites for ORR . Moreover, the interaction between Co and N in the Co−N bonds (399.1 eV) increases active sites and improves the ORR performance due to the electron density redistribution . Accordingly, the total amount of N in CoO/NC2 was estimated to be 2.56 at.% by XPS analysis.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Notably, the pyridinic and graphitic nitrogen, considered to be the most efficient active sites of all the nitrogen species in CoO/NC are able to not only enhance the initial chemical adsorption of oxygen on the catalyst surface but increase the number of catalytically active sites for ORR . Moreover, the interaction between Co and N in the Co−N bonds (399.1 eV) increases active sites and improves the ORR performance due to the electron density redistribution . Accordingly, the total amount of N in CoO/NC2 was estimated to be 2.56 at.% by XPS analysis.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 1, XRD analysis confirmed the crystallographic structure of the specimens prepared using the spray pyrolysis process. It was observed that Ketjenblack has a relatively broad peak near 268 for a graphitic carbon plane (002) without sharp peaks for different elements, [29][30][31] . This means that the cobalt nitrate used as the precursor was completely decomposed and oxidized to cobalt(II) oxide during spray pyrolysis at a reaction temperature of 600 8C and a short residence time (< 4 s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, one of the effective methods is to regulate the specific surface area and pore size of the catalyst and thus expose more active sites . Some researchers use porous carbon support materials such as carbon aerogel (CA) or graphene foam and further control their morphology for this purpose . In some studies, a template method is used to increase the specific surface area of carbon supports .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Some researchers use porous carbon support materials such as carbon aerogel (CA) or graphene foam and further control their morphology for this purpose. [22][23][24] In some studies, a template method is used to increase the specific surface area of carbon supports. [25][26][27] Recently, metal organic frameworks (MOFs), as developing kinds of periodic porous three-dimensional framework polymers, have also been widely used in ORR catalysts.…”
Section: Introductionmentioning
confidence: 99%